Abelhas visitantes das flores do urucuzeiro (Bixa orellana L.) e suas eficiências de polinização - Mesquita, Francisca Ligia Aurelio (2008)
The research was carried out in the farm Kiara Coeli situated in the county of Caucaia, state of Ceará, Brazil. Data gathering took place from March to August 2007. In a 6ha crop made up of hybrids annatto plants. The work aimed to know the pollination requirements of annatto (Bixa orellana L.), to identify its floral visitors and the pollination efficiency of the most frequent floral visitors. Pollination requirements were evaluated by means of studies in floral biology, stigma receptivity and treatments of open pollination, hand cross pollination, self-pollination, muslin bag restricted pollination and paper bag restricted pollination; floral visitors were captured for identification and their frequency and foraging behavior were observed using transects which were walked in a regular basis throughout the day. Pollination efficiency of the most frequent floral visitors was assessed allowing one-floral visit only, and measurements of size, weight and number of seeds produced per fruit. Results showed that the annatto flowers last only one day and bear poricidal anthers that need to be vibrated to release pollen, are receptive only in the morning shift, especially between 9:30 and 10:30 h, and produce significantly (p<0,05)more fruits under cross pollination than self-pollination. Flowers were visited by insects of the Orders Diptera, Coleoptera and Hymenoptera, mainly 13 bee species belonging to the families Antophoridae, Apidae, Halictidae and Andrenidae, namely: Xylocopa frontalis, Xylocopa grisensces, Xylocopa muscaria, Exomalopsis analis, Apis mellifera, Melipona subnitida, Partamona sp., Trigona spinipes, Eulaema nigrita, Euglossa sp, Megalopta sp.,Augochloropsis sp. and Oxaea sp. Bees collected exclusively pollen, mainly early in the morning and varied (p<0,05) in frequency to flowers, foraging behavior and pollinating efficiency with only one floral visit. It was concluded that pollination in annatto is mainly xenogamous and dependent upon biotic agents, especially bees; the floral visitor’s foraging behavior is of paramount importance to determine its pollination efficiency of annatto flowers, and the bee species Xylocopa frontalis, Augochloropis sp. and Eulaema nigrita, by order of importance, were the most effective pollinators in the studied area, and their presence should be improved in the site.